Effectiveness of Wordwall Education Games (Gaull) to Improve Reading and Writing Skills of 1st Grade Elementary School Students - Nursanti, Ika; Anggraini, Deri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to test the effectiveness of the wordwall education game on improving the reading and writing skills of first-grade elementary school students. This study applies a quasi-experimental method through the "Nonequivalent Control Group Design" design. In its implementation, this study included two groups of subjects, namely the control group and the experimental group. The control group was given learning through word cards, while the experimental group was given through the wordwall education game media. Both groups were then given an initial reading and writing ability test, the results of which were analyzed using IBM SPSS software. The results of the analysis showed a significant value of 0.000 in the reading aspect and 0.006 in the writing aspect, which means that Ho was rejected and H1 was accepted, through the "Independent Sample T-test", meaning that a significant difference was obtained in reading and writing abilities between the compared groups. These findings show that the application of the wordwall education game media is effective in improving the initial reading and writing skills of first-grade elementary school students.